2018
DOI: 10.1016/j.reth.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with an angiotensin II receptor blocker abolished ameliorating actions of adipose-derived stem cell sheets on cardiac dysfunction and remodeling after myocardial infarction

Abstract: IntroductionCell sheets using myoblasts have been developed for the treatment of heart failure after myocardial infarction (MI) bridging to heart transplantation. Stem cells are supposed to be better than myoblasts as a source of cells, since they possess a potential to proliferate and differentiate into cardiomyocytes, and also have capacity to secrete angiogenic factors. Adipose-derived stem cells (ASCs) obtained from fat tissues are expected to be a new cell source for ASC sheet therapies. Administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…Isolation and coronary perfusion of hearts were conducted by using a Langendorff perfusion system (Model 7523-40; Masterflex, Barrington, IL, USA), as described previously. 18 Coronary arteries were perfused with a modified Tyrode's solution (NaCl 144, KCl 5, CaCl2 1.5, MgCl2 0.9, HEPES 6, and D-glucose 5 [in mmol/L]; pH 7.4 with NaOH) equilibrated with 100% oxygen. D-luciferin (Toyobo, Osaka, Japan) of 25 μmol (1 mL of 25 mmol/L solution) was injected into coronary arteries of MI hearts through the aorta.…”
Section: Ex Vivo Imaging Of Langendorf Rat MI Hearts Transplanted Witmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and coronary perfusion of hearts were conducted by using a Langendorff perfusion system (Model 7523-40; Masterflex, Barrington, IL, USA), as described previously. 18 Coronary arteries were perfused with a modified Tyrode's solution (NaCl 144, KCl 5, CaCl2 1.5, MgCl2 0.9, HEPES 6, and D-glucose 5 [in mmol/L]; pH 7.4 with NaOH) equilibrated with 100% oxygen. D-luciferin (Toyobo, Osaka, Japan) of 25 μmol (1 mL of 25 mmol/L solution) was injected into coronary arteries of MI hearts through the aorta.…”
Section: Ex Vivo Imaging Of Langendorf Rat MI Hearts Transplanted Witmentioning
confidence: 99%
“…ADSCs were isolated from the inguinal subcutaneous fat tissue of 8-week-old wild-type (WT) Lewis rats and Tg rats of the same strain, and cultured as described previously. 18,19 To prepare cell sheets, ADSCs were cultured on 35-mm temperature-responsive culture dishes (UpCell, Cell Seed Inc., Tokyo, Japan) in an incubator at 37°C for 48 h. They were then maintained at 20°C for 1 h and were detached as an intact sheet.…”
Section: Engineering Of Adsc Sheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that ADSC-derived cell sheet could attenuate cardiac dysfunction with scarred myocardium repair, cardiac remodeling attenuation, increased cellular engraftment, upregulated growth factor and cytokine expression, decreased interstitial fibrosis, and increased capillary density in border areas [66,67]. Interestingly, an angiotensin II receptor blocker, irbesartan, was observed to abolish the effects of rat ADSC-derived cell sheet on the attenuation of cardiac dysfunction and remodeling in a 5-week AMI rat model [68]. Moreover, Imanishi and his colleagues reported that the transplantation of adipocyte-derived sheet 5 min after AMI surgery ameliorated inflammation and inhibited fibrosis in a mouse AMI model after 2 days or 28 days [47].…”
Section: Mesenchymal Stem Cell-derived Cell Sheetmentioning
confidence: 99%
“…Hypoxia, as a major stress-inducing angiogenesis, can enhance the therapeutic effects of cell sheet in MI via increased vascularization [45]. An angiotensin II receptor blocker, irbesartan, observably abolished the effects of rat ADSC-derived cell sheet on the attenuation of cardiac dysfunction and remodeling in a 5-week MI rat model [68]. It is known that SMs do not easily develop synchronized beating with the host heart; however, studies have shown that improved systolic and diastolic functions exist in the host AMI heart after myoblast transplantation, even without contraction of the transplanted myoblasts, and observable angiogenesis was detected in the transplanted regions, indicating a plausible reason for the role of cell sheet in heart contraction recovery after MI [89,90].…”
Section: Paracrine Effects and Neovascularizationmentioning
confidence: 99%